2000
DOI: 10.2519/jospt.2000.30.10.602
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lateral Slide Exercise in an Anterior Cruciate Ligament Reconstruction Rehabilitation Home Exercise Program

Abstract: --7 . 7 -cl...l...clr-l.r r r rrrrrrrn r . . *. r r cr I -r --.--r -, Study Design: Two-group repeated measures design using a sample of convenience of subjects with anterior cruciate ligament (ACL) reconstructive surgery. Objectives: To determine the effect of incorporating one specific weight-bearing exercise (lateral slide exercise using a slide board) into an ACL reconstruction home exercise program. Background: Reduced clinic visits have increased the importance of home exercise programs in knee ligament … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
1
11
0
3
Order By: Relevance
“…Based on a hypothesized 10–12% difference in PeakTT between the two groups, the number of participants required to achieve a power of greater than 0.85 was estimated by power analysis. The number of participants used (per group) in this study is comparable to published prospective ACL rehabilitation studies (Ihara & Nakayama, 1986; Blanpied, Carroll, Douglas, Lyons, Macalisang, Pires, 2000; Wojtys, Huston, Taylorm, Bastian, 1996).…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…Based on a hypothesized 10–12% difference in PeakTT between the two groups, the number of participants required to achieve a power of greater than 0.85 was estimated by power analysis. The number of participants used (per group) in this study is comparable to published prospective ACL rehabilitation studies (Ihara & Nakayama, 1986; Blanpied, Carroll, Douglas, Lyons, Macalisang, Pires, 2000; Wojtys, Huston, Taylorm, Bastian, 1996).…”
Section: Methodssupporting
confidence: 55%
“…Thus, there is the likelihood that this study was underpowered to demonstrate differences between the two groups in the secondary outcome measures. However, other published ACL rehabilitation studies have used similar number of participants per group (Ihara & Nakayama, 1986; Blanpied et al, 2000; Wojtys et al, 1996). Also, despite the small sample size used, this study revealed a significant interaction effect between the type and the duration of training on neuromuscular function.…”
Section: Limitationsmentioning
confidence: 99%
“…Blanpied et al, 3 in a 2000 study, assessed the effectiveness of adding a slide board home exercise program 2 times per week to a standard physical therapy regimen. Fourteen patients were randomly assigned to 2 groups 8 weeks following ACL reconstruction using a bonepatellar tendon-bone autograft.…”
Section: Miscellaneousmentioning
confidence: 99%
“…After 3 weeks, each subject was instructed to do closed kinetic chain (CKC) exercises such as squats and lateral step-ups with gradual body-weight bearing. [15][16][17] After 4 weeks, bike exercises were commenced. At 3 months postsurgery, most subjects were able to fully extend the knee and commenced walking/running exercises.…”
Section: Rehabilitation Proceduresmentioning
confidence: 99%